Tin sulfide modified separator as an efficient polysulfide trapper for stable cycling performance in Li–S batteries. Issue 1 (25th September 2018) - Moorthy, Brindha; Kwon, Soonho; Kim, Joo-Hyung; Ragupathy, P.; Lee, Hyuck Mo; Kim, Do Kyung
Abstract : Lithium–sulfur batteries (Li–S) are considered the most promising systems for next-generation energy storage devices due to their high theoretical energy density and relatively low cost. Abstract : Lithium–sulfur batteries (Li–S) are considered the most promising systems for next-generation energy storage devices due to their high theoretical energy density and relatively low cost. However, the practical applications of Li–S batteries are hindered by the poor electronic conductivity of sulfur and capacity degradation resulting from the shuttle effect of lithium polysulfides (LiPSs). Herein, we demonstrate use of a tin-sulfide (SnS2 ) modified separator to facilitate the redox reaction involving LiPS intermediates and realize improved electrochemical performance in a Li–S battery. Density functional theory (DFT) calculations revealed that SnS2 exhibits a strong affinity with LiPSs and induces a rapid conversion of trapped polysulfides. As a result, Li–S batteries with a SnS2 -modified separator exhibited an enhanced specific capacity of 1300 mA h g −1 at 0.2C (corresponding to a high areal capacity of 4.03 mA h cm −2 ), which was maintained at 1040 mA h g −1 after 150 cycles. Furthermore, an excellent rate capability is achieved with a capacity of 700 mA h g −1 (2.17 mA h cm −2 ) at 5C. Additionally, the modified separator exhibited excellent cycling performance up to 500 cycles at 2C, with a low capacity decay rate of 0.0710% per cycle. The excellent performance of the sulfur electrode is mainly attributed to the incorporation of the SnS2 coating layer on the separator, which effectively confines polysulfides via both chemical and physical interaction and rapidly improves lithium ion diffusion. Moreover, the SnS2 coating layer greatly improves sulfur utilization and efficiently accelerates the kinetic conversion of trapped polysulfides.